2003
DOI: 10.1002/fut.10083
|View full text |Cite
|
Sign up to set email alerts
|

Scheduled announcements and volatility patterns: The effects of monetary policy committee announcements on LIBOR and short sterling futures and options

Abstract: Both the UK spot and futures markets in short‐term interest rates are found to react strongly to surprises in the scheduled announcements of the repo rate and RPI. Therefore, these announcements should also affect the market for options on short‐term interest rate futures. Because the repo rate and RPI announcements are scheduled, the options market can predict the days on which announcement shocks may hit, and build this information into its volatility expectations. It is argued that the volatility used in pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 50 publications
(89 reference statements)
0
5
0
Order By: Relevance
“…These articles use autoregressive conditional heteroskedasticity (ARCH) modeling or other time-series-based volatility estimates to assess the impact of macroeconomic news on bond market uncertainty. Although the time-series-based volatility estimates are by construction constrained to be ex post, an ex ante perspective with volatilities implied by option prices is taken in Ederington and Lee (1996), Fornari and Mele (2001), Heuson and Su (2003), and Sun and Sutcliffe (2003). 3 Regardless of the approach, the existing literature demonstrates that bond market volatility is mostly affected by inflationary and unemployment news.…”
Section: Introductionmentioning
confidence: 99%
“…These articles use autoregressive conditional heteroskedasticity (ARCH) modeling or other time-series-based volatility estimates to assess the impact of macroeconomic news on bond market uncertainty. Although the time-series-based volatility estimates are by construction constrained to be ex post, an ex ante perspective with volatilities implied by option prices is taken in Ederington and Lee (1996), Fornari and Mele (2001), Heuson and Su (2003), and Sun and Sutcliffe (2003). 3 Regardless of the approach, the existing literature demonstrates that bond market volatility is mostly affected by inflationary and unemployment news.…”
Section: Introductionmentioning
confidence: 99%
“…This builds on a body of work that has examined the relation between volatility implied by options markets and news releases. For example, Bailey (1988), Ederington and Lee (1993,1996, Nofsinger and Prucyk (2003) and Sun and Sutcliffe (2003) have all explored the relation between macroeconomic announcements and the implied volatilities of options on a variety of underlying financial securities, while Wolfson (1979),(1981), Donders and Vorst (1996) and Acker (2002), among others, have examined the relation between stock option implied volatilities and microeconomic news. That research suggested that volatility reduced after news releases as uncertainty was resolved.…”
mentioning
confidence: 99%
“…To capture the actual content of macroeconomic news announcements and examine their effects, previous studies use surprise components (Bailey, ; Balduzzi et al, ; Sun & Sutcliffe, ). Following Balduzzi et al (), we estimate the regression model in the following equation, which includes a surprise component: dlog(italicIVOLitalicimt)=β0+normal∑m=14αmIm+normal∑m=14δm(true|SURPittrue|×Im)+italicCONTROLitalicimt+eitalicimt,where IVOL is the volume‐weighted implied volatility ( IV ), call‐implied volatility ( IV_CALL ), or put‐implied volatility ( IV_PUT ) and SURP is the absolute value of a standardized measure of the surprise contained by macroeconomic news announcement i on day t (from Equation ).…”
Section: Empirical Findingsmentioning
confidence: 99%
“…To capture the actual content of macroeconomic news announcements and examine their effects, previous studies use surprise components (Bailey, 1988;Balduzzi et al, 2001;Sun & Sutcliffe, 2003). Following Balduzzi et al (2001), we estimate the regression model in the following equation, which includes a surprise component:…”
Section: Market Responses To News Surprisesmentioning
confidence: 99%